Study on Nursing Effect of Psychological Intervention on Uremic Hemodialysis Patients. (13th July 2022) - Chen, Yan; Ding, Jie; Li, Chunqing; Wu, Ting; Li, Qingya; Chen, Rujing; Zhou, Jingfen
Abstract : Aim . Patients in the hemodialysis stage are prone to psychological pressure of depression and anxiety and have resistance, which affects the clinical treatment effect. Effective psychological intervention plays a very important role in improving patients' psychological pressure and patients' compliance. The aim of this study is to explore the nursing effect of psychological intervention on uremic hemodialysis patients. Methods . There were 126 uremic hemodialysis patients admitted to the hospital from August 2020 to December 2021. The patients were randomly divided into the routine nursing care group (n = 63 ) and psychological intervention group (n = 63 ). The routine nursing care group received routine nursing care for uremia hemodialysis patients. The psychological intervention group implemented psychological intervention on uremia hemodialysis patients. The methods of psychological intervention mainly include establishing a good nurse-patient relationship, popularizing hemodialysis knowledge, timely psychological counseling for patients, and organizing patient communication meetings. The treatment compliance, Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) of the two groups were compared before and after nursing. SF-36 scale was used to evaluate the quality of life of patients. The incidence of complications and nursing satisfaction were compared between the two groups. Results . The treatment compliance rate and nursing satisfaction of hemodialysis uremic patients in the psychological intervention group were significantly higher than the routine nursing care group. The SAS and SDS of hemodialysis uremia patients in the psychological intervention group were significantly lower than the routine nursing care group after psychological intervention, and SF-36 scale was significantly higher than the routine nursing group. The main complications of uremic hemodialysis patients are hypotension, hyperkalemia, internal fistula occlusion, and infection. Compared with the routine nursing care group, the incidence of complications in the psychological intervention group was significantly reduced. Conclusion . The implementation of psychological nursing intervention for uremic hemodialysis patients have a very significant effect on reducing the incidence of complications and improving anxiety, depression, treatment compliance, and the quality of life and the nursing satisfaction.